Nonspecific eating disorders: ortorexia nervosa and night eating syndrome - a subjective review - Patrycja Potyrała; Dominik Olejniczak (Kazimierz Wielki University, 2018)
Eating habits pose an import factor which influences our health state. Nowadays two main tendencies prevail in the society: following the rules of healthy eating conscientiously, whereas the other one consists in using food as a tool serving to mood improvement. The article is devoted to non-specific eating disorders, that is, night eating syndrome (NES) and orthorexia nervosa. Orthorexia nervosa is an affixation on healthy eating, whereas night eating syndrome is a night-time hypherphagia, morning anorexia and insomnia. At present, it seems that these two disorders are not frequent. The misthinking may be caused by difficulties in diagnosing them. The identification can be stymied by the lack of unified definition or the lack of unified diagnostic criteria. Further researches of these health problems are recommended as in the future they may cause development of a lot of serious diseases. One must pay attention, in particular, to night eating syndrome and its importance in obesity development and its link to type 2 diabetes.